Factors Affecting the Incidence of Anemia in Pregnant Women at Ampel and Gladagsari Public Health Center Boyolali Regency in 2019 - Davidson, Sarah Melati; Mangalik, Gelora; Riswandha, Rifki Ilham (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2022)
Background: Anemia is a condition where the blood hemoglobin level is <11 g/dl. Anemia is often experienced by mothers during pregnancy. The main cause of anemia in pregnant women is due to iron deficiency in the body. This study aims to determine what factors are the main causes of anemia in the working area of Ampel Health Center and Gladagsari Health Center. Poor nutritional status, parity, short pregnancy intervals are believed to be the biggest contributors to the incidence of anemia in pregnant women.Methods: This study used secondary data with a cross sectional design. Chi Square test is used in statistical testing. Study involved Ampel Health Center (193 samples) and Gladagsari Health Center (246 samples). The variables studied were the age of pregnant women, distance between pregnancies, parity, nutritional status, Antenatal Care and adherence to Fe tablet consumption.Results: The results showed that nutritional status (0.001), gestational distance (0.003), parity (0.032) and age of pregnant women (0.032) had a significant relationship with the incidence of anemia in Ampel Health Center < (0.05). Gladagsari Health Center samples showed different results where nutritional status (0.003), gestational distance (0.007), parity (0.005), adherence to Fe tablet consumption (0.049) and age of pregnant women (0.046) had a significant relationship with the incidence of anemia < (0, 05). Maternal nutritional status during pregnancy is the highest cause of anemia, many steps can be taken to improve the nutritional status of pregnant women, one of which is the provision of additional food.Conclusion: Education of health workers about the importance of consuming Fe tablets for women of childbearing age (WUS) and pregnant women and self-compliance play an important role in preventing anemia during pregnancy.